Hermeneutika Keadilan dalam Ayat Poligami: Antara Ideal Moral Dan Pratik Sosial - Novika, Fatchiyah Ayu; Asmuni, Asmuni (PT. Sharia Journal and Education Center, 2026)
The Quranic verses 3 and 129 of Surah An-Nisa, which discuss polygamy, remain a hot topic of debate in Islamic Family Law studies. This is particularly true regarding the justice intended as a prerequisite for the permissibility of polygamy. In social reality, polygamy is often practiced solely in accordance with formal law without considering the deeper aspects of justice, namely the ethical and humanitarian aspects that constitute the primary objectives of the Quran. This article aims to analyze the meaning of justice in the verses on polygamy through a hermeneutical approach and examine the gap between the moral ideals outlined in the Quranic verses and the practice of polygamy in society. The research method employed is descriptive-normative, analyzing Quranic verses through classical and contemporary interpretations as well as literature related to hermeneutical theory and Islamic family law. The results indicate that justice in the Quranic verses 3 and 129 of Surah An-Nisa encompasses not only material justice but also justice in substance, psychology, and human dignity. From a hermeneutical perspective, polygamy is interpreted as a limited and conditional social solution, rather than a goal. Thus, the ethical principles of the Quran consider monogamy as the form of relationship closest to the principle of justice. This article examines the significance of understanding polygamy in relation to substantive justice, the protection of women, and the social dynamics of modern society.